Ibis Paint X Module Development to Improve Students' Competency in Digitally Designing Daily Wear Fashion Designs for the Gen Z Era - Analia Susanti; Yeri Sutopo; Sri Endah Wahyuningsih; Eko Supraptono (Universitas Negeri Semarang, 2026)
Development digital technology has become imperative in the world of industry and education, demands adaptation curriculum School Intermediate Vocational (SMK) to be able to produce source Power human beings who have competence in accordance the needs of the world of work, especially in fashion design field. Learning conventional which tends to theoretical need innovation with utilise technology digital -based for create a more effective learning process active, creative, and relevant with style life of Gen Z. Therefore that, research This focus on four objectives main: (1) Produce module-based Ibis Paint X application with draft mood board for design fashion digital ready-to-wear; (2) Analyze level eligibility module; (3) Analyze level practicality module in context of learning model Problem-Based Learning (PBJL); and (4) Analyzing effectiveness module in increase ability increase competence student in manufacturing design fashion daily wear era gen z digitally. Study This use approach Research and Development (R&D) with adopting the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Subject study is vocational school students in the subject lesson design fashion. Data analysis includes feasibility tests, practicality tests, and effectiveness tests. use N-Gain Score and statistical test t-Test N-Gain Score. N-Gain is related with increase competence student in manufacturing design fashion Daily wear in the Gen Z era digitally. Reliability test results to evaluation eligibility modules by experts’ material get mark of 0.898. Validation results expert show that developed modules is in the very appropriate category, confirms suitability content and construction module in a way academic. Practicality test in PBJL implementation shows very practical category. More further, the results of the effectiveness test prove that Ibis Paint X module is very effective in increase competence student in manufacturing design fashion daily wear era gen z digitally. This is supported by the acquisition N-Gain value of 81% (category effective) and the results of the t-test show Sig. value (2-tailed) of 0.000 < 0.001, which is far smaller from level significance of 0.05. This result confirms existence improvement competence student in manufacturing design fashion daily wear era gen z digitally significant after use module